2016
DOI: 10.1371/journal.pone.0167152
|View full text |Cite
|
Sign up to set email alerts
|

Rice Yield and the Fate of Fertilizer Nitrogen as Affected by Addition of Earthworm Casts Collected from Oilseed Rape Fields: A Pot Experiment

Abstract: The mechanism associated with improvement of soil nutritional status by oilseed rape crop, leading to better performance of rice crop, in rice-oilseed rape cropping systems is little known. The present study was aimed to test the hypothesis that earthworm casts produced during oilseed rape-growing season have positive effects on grain yield and fertilizer nitrogen (N) utilization in the subsequent flooded rice crop. A 15N-tracing pot experiment was conducted to determine the effects of earthworm casts collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Results showed that with the exception of pH, the contents of total nitrogen, Mehlich III P and K, and organic matter in soils were lower at harvesting than before planting (Table 1), and there was no difference in these measurements between nitrogen treated groups and the control. This observation suggests that in addition to have been absorbed by the rice plants, some of the applied nitrogen fertilizers may have lost via denitrification, and hence resulting in a lower total nitrogen concentration after planting (Fillery and Vlek 1982;Huang et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that with the exception of pH, the contents of total nitrogen, Mehlich III P and K, and organic matter in soils were lower at harvesting than before planting (Table 1), and there was no difference in these measurements between nitrogen treated groups and the control. This observation suggests that in addition to have been absorbed by the rice plants, some of the applied nitrogen fertilizers may have lost via denitrification, and hence resulting in a lower total nitrogen concentration after planting (Fillery and Vlek 1982;Huang et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, decreasing inorganic fertilizer use may solve environmental issues. Other studies showed that decreasing N rates from 0.74 g pot −1 (equivalent to the recommended field rate of 150 kg ha −1 ) to 0.44 g pot −1 (equivalent to 60% of the recommended rate) resulted in lower fertilizer N loss rates [27].…”
Section: Effects Of Organic Fertilizer In the Fieldmentioning
confidence: 97%
“…Calculations and statistical analyses. Plant N uptake derived from fertilizer and soil was calculated as follows (Huang et al 2014(Huang et al , 2016:…”
Section: Methodsmentioning
confidence: 99%